IMS centric communication supporting WebRTC endpoints - Cruz, Bruno Simões (2016)
With the evolution of technologies such as WebRTC and telecommunication (Telco) architectures aligned with the latest 3GPP standards, the search for interoperability between traditional and web-oriented endpoints is vital, with new use-cases and multimedia services to be explored. Currently, convergence goes beyond the standards and, as such, its search and the technological obstacles motivate this work. We make a proposal for the implementation of a platform uniting state-of-the-art Telco networks with WebRTC technologies. To validate the solution, an IMS integrated prototype was built, being evaluated in terms of call throughput and system induced mouth-to-ear delay. Results show that call delay is on par with current mobile network calls, making the current solution a viable alternative for communication bridging in a Telco network.